Komik Digital Reyog Sebagai Upaya Membangun Karakter Religius Anak - Happy Susanto; M. Zainal Arif; Anip Dwi Saputro; Sigit Dwi Laksana; Moh. Tajab; Ja'far Arifin (MUADDIB Jurnal Kependidikan dan Keislaman, 2022)
Digital comics are interesting learning media for students. With the existence of digital comics, it makes learning more fun and has its own characteristics. If cultural arts are taught with learning media, especially the art of Reyog Ponorogo, students are more familiar with cultural values and their development.In order to build religious character in students, digital comic learning media is an effort to grow Islamic values. In digital comics there are interesting pictures so that students are more enthusiastic in learning.This study uses a literature study method using primary and secondary data sources for primary data reviewing previous research, secondary data researchers are directly in the field.It is hoped that with the Reyog digital comic learning media in addition to introducing and preserving it, students can form religious characters so that they prioritize cultural and religious aspects.